2008
DOI: 10.1182/blood-2007-11-122010
|View full text |Cite
|
Sign up to set email alerts
|

CYP4F2 genetic variant alters required warfarin dose

Abstract: Warfarin is an effective, commonly prescribed anticoagulant used to treat and prevent thrombotic events. Because of historically high rates of drug-associated adverse events, warfarin remains underprescribed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
381
10
12

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 468 publications
(438 citation statements)
references
References 35 publications
30
381
10
12
Order By: Relevance
“…Caldwell et al 19 studied three independent white US cohorts and found a 4-12% increase in warfarin dose per T allele. On the basis of the frequency distributions of the derived T allele (30% among Europeans and Asians vs approximately 7% in Africans), these authors suggested that the expected contribution of this SNP to stable warfarin dose in Africans will be lower than in Europeans and Asians.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Caldwell et al 19 studied three independent white US cohorts and found a 4-12% increase in warfarin dose per T allele. On the basis of the frequency distributions of the derived T allele (30% among Europeans and Asians vs approximately 7% in Africans), these authors suggested that the expected contribution of this SNP to stable warfarin dose in Africans will be lower than in Europeans and Asians.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has identified a third gene, CYP4F2 as influencing an individual's sensitivity to warfarin. 9,19,20 CYP4F2 codes for a vitamin K 1 oxidase that causes a decrease in the metabolism of vitamin K 1 . 21 Several studies have shown that carriers of the derived T allele at the non-synonymous SNP rs2108622 require higher warfarin doses than subjects with the ancestral C allele.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caldwell et al 54 reported a CYP2C9 variant in CYP4F2 associated with warfarin dose in white patients who were receiving a stable dose of warfarin. Takeuchi et al 55 estimated that the CYP4F2 accounted for 1.5% of the effect on warfarin dose.…”
Section: Effect Of Allelic Variants On Warfarin Activitymentioning
confidence: 99%
“…Il faut donc définir la dose à l'équilibre pour chaque patient afin d'obtenir une bonne efficacité thérapeu-tique avec un risque hémorragique minimum. Après des recherches à l'aide des approches gène-candidat, les polymorphismes des gènes codant pour le cytochrome P4502C9 (CYP2C9), la vitamine K époxyde réductase (VKORC1) [29] et le cytochrome P4504F2 (CYP4F2) ont été significativement associés à la variabilité de réponse à la warfarine par des approches de génomique (genome-wide) [9][10][11]. Ainsi, les génotypes de CYP2C9, de VKORC1 et de CYP4F2, l'âge et le poids permettent d'expliquer 60,5 % de la variabilité interindividuelle de la dose à l'équilibre de la warfarine [12].…”
Section: Les Mécanismes Physiopathologiques Des Réactions Idiosyncratunclassified